Malevolent Monitoring: Dark Triad Traits, Cyber Dating Abuse, and the Instrumental Role of Self-Control - Schokkenbroek, Janneke M. (Journal of interpersonal violence, 2024)
Cyber dating abuse (CDA) concerns the use of digital technology to control, monitor, and hurt one’s intimate partner. CDA can have profound detrimental outcomes, such as mental health problems. As such, it is important to identify intrapersonal factors that may explain these behaviors. Previous research suggests that one such factor is the personality cluster of Dark Triad traits (DTT), comprising Machiavellianism, narcissism, and psychopathy. Additionally, DTT and CDA perpetration have both been linked to poor self-control ability, but these relationships have not yet been tested together in one model. As such, the present study examines if individuals’ poor self-control ability mediates the relationship between the DTT and CDA perpetration. To test these associations, we conducted a survey study among a representative sample of Belgian adults (n = 1,144; Mage = 47.66 years; 51.3% female). Findings from correlation analyses revealed that all three DTT were individually associated with CDA perpetration, such that higher scores on these traits corresponded with more CDA perpetration. Additionally, pathway analyses from structural equation modeling revealed that individuals’ poor self-control ability fully explained the relationship between Machiavellianism and narcissism and CDA perpetration, and partially explained the relationship between psychopathy and CDA perpetration. As our findings suggest that self-control plays an instrumental role in explaining why individuals control and monitor their partner via digital technology, prevention and intervention efforts should seek ways to improve individuals’ self-control ability in situations that may trigger such harmful interpersonal behaviors, particularly among individuals who exhibit Dark Triad personality traits.